Potentiometric urea biosensors - Ozbek, Oguz; Berkel, Caglar; Isildak, Omer; Isildak, Ibrahim (ELSEVIER, 2022)
Excess nitrogen in the body is converted to urea in the liver, and urea is disposed as a waste product in urine. Urea concentration can change in body fluids such as blood due to the presence of certain disorders. Therefore, the determination of urea is of high importance in various areas including medical diagnosis, as well as food quality control and environmental monitoring. Potentiometric sensors have certain advantages over their alternatives, such as rapidity, portability, cost effectiveness, high sensitivity, easy operation and simple apparatus. Potentiometric urea biosensors based on enzyme urease have been developed using various materials including nanoparticles and films, and also using different methodologies. In this review, we covered potentiometric urea biosensors reported in the literature, and touched upon their certain structure characteristics and performance parameters including detection limit, working concentration range, response time and lifetime, all of which are of practical importance. Each potentiometric urea biosensor has its own advantages and drawbacks, thus the selection of appropriate method depends on the sample to be analyzed, its urea concentration range and other requirements of the particular application. Further research is needed in order to optimize the performance of these devices and to broaden their applicability.
Keywords: Urea; Potentiometry; Biosensor; Biomedical analysis; Clinical chemistry; Medical diagnosis; RECOMBINANT UREASE; CARBON NANOTUBES; SENSOR; ELECTRODE; IMMOBILIZATION; NANOPARTICLES; POLYANILINE; MEMBRANE; COMPLEX; SYSTEM; Medical Laboratory Technology